Product Placement Dalam Serial Drama Korea (Analisis Isi Kualitatif terhadap Evaluasi Atribut Product Placement Kopiko dalam Drama Korea Vincenzo) - Rahma Praminia, I Gusti Agung Ayu (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2024)
This study aims to analyze the implementation of Kopiko product placement in the Korean drama "Vincenzo" through Russell's (2002) dimensions of product placement, while evaluating the associated attributes of Kopiko brand placement within it. Considering the attributes of Entertainment, Informativeness, and Discomfort as outlined by Ducoffe (1996), the study adopts a qualitative approach with a constructivist paradigm, utilizing content analysis as the research method. The units of analysis include episodes 14, 15, 17, and 19 of the drama "Vincenzo". The analysis results indicate that the product placement strategy successfully optimizes visual, entertainment, and informative attributes in each episode. Aligning product messages with the storyline is crucial to maintaining narrative integrity without disrupting the viewer's experience. For instance, dialogues promoting the consumption of Kopiko candies in specific scenes demonstrate effective alignment between product messaging and narrative context. The informative attribute of product placement is also demonstrated effectively, particularly in episode 19 where information about Kopiko's product advantages is conveyed through dialogue, providing added value to viewers with relevant product information aligned with product placement attributes. Nevertheless, there is a risk of discomfort from product placement if the integration of the product within the storyline is inadequate. This study underscores the importance of considering product integration with a consistent narrative to avoid disruptions to the viewer's experience.ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi product placement Kopiko dalam drama Korea Vincenzo melalui dimensi product placement oleh Russell (2002), serta mengevaluasi atribut-atribut product placement yang terkait dengan merek Kopiko di dalamnya. Dengan mempertimbangkan atribut Entertainment, Informativeness, dan Discomfort sebagaimana dijelaskan oleh Ducoffe (1996). Metode yang digunakan adalah pendekatan kualitatif dengan paradigma konstruktivisme, menggunakan analisis isi sebagai jenis penelitian. Unit observasi yang dianalisis adalah episode 14, 15, 17, dan 19 dari drama Korea Vincenzo. Hasil analisis menunjukkan bahwa strategi product placement berhasil mengoptimalkan atribut visual, hiburan, dan informatif dalam setiap episode. Penyesuaian pesan produk dengan alur cerita menjadi kunci utama untuk menjaga integritas naratif tanpa mengganggu pengalaman menonton. Seperti dialog yang mengarahkan konsumsi permen Kopiko dalam adegan tertentu menunjukkan penyesuaian yang baik antara pesan produk dan konteks cerita. Atribut informatif dari product placement juga terbukti efektif, terutama pada episode 19 di mana informasi mengenai kelebihan produk Kopiko disampaikan melalui dialog, yang memberikan nilai tambah kepada penonton dengan informasi yang relevan sesuai dengan atribut. Meskipun demikian, risiko ketidaknyamanan dari product placement dapat terjadi jika produk tidak terintegrasi dengan baik dalam cerita. Penelitian ini menyoroti pentingnya mempertimbangkan integrasi produk dengan naratif yang konsisten untuk menghindari gangguan pada pengalaman penonton.